Fast operando X‐ray pair distribution function using the DRIX electrochemical cell. (10th July 2020) - Diaz-Lopez, Maria; Cutts, Geoffrey L.; Allan, Phoebe K.; Keeble, Dean S.; Ross, Allan; Pralong, Valerie; Spiekermann, Georg; Chater, Philip A.
Abstract : The Diamond Radial In Situ X‐ray (DRIX) cell for combining electrochemical cycling with total scattering measurements is presented and applied to X‐ray pair distribution function and X‐ray Raman scattering studies on the high‐capacity cathode material Li4 Mn2 O5 . Abstract : In situ electrochemical cycling combined with total scattering measurements can provide valuable structural information on crystalline, semi‐crystalline and amorphous phases present during (dis)charging of batteries. In situ measurements are particularly challenging for total scattering experiments due to the requirement for low, constant and reproducible backgrounds. Poor cell design can introduce artefacts into the total scattering data or cause inhomogeneous electrochemical cycling, leading to poor data quality or misleading results. This work presents a new cell design optimized to provide good electrochemical performance while performing bulk multi‐scale characterizations based on total scattering and pair distribution function methods, and with potential for techniques such as X‐ray Raman spectroscopy. As an example, the structural changes of a nanostructured high‐capacity cathode with a disordered rock‐salt structure and composition Li4 Mn2 O5 are demonstrated. The results show that there is no contribution to the recorded signal from other cell components, and a very low and consistent contribution from the cell background.